(untitled) (Asian Journal of Agriculture, 2024)
Abstract. Yudistira DH, Sandi YU, Wirabumi BA, Damayanti A, Wikandari P, Sato S. 2025. Effects of different application doses of black soldier fly frass Hermetia illucens (Diptera: Stratiomydae) on soybean plant performances and arthropod abundance. Asian J Agric 9: 40-51. Food waste poses a global challenge, contributing approximately 3.49 billion tons of CO2 to the atmosphere annually. Recycling this waste into valuable soil nutrients is a viable solution. This study focuses on black soldier fly Hermetia illucens L. (Diptera: Stratiomydae) larvae, which convert organic waste into protein-rich biomass and frass, a potential soil amendment. However, the effects of black soldier fly frass on crop performance and biodiversity remain underexplored. We investigated the impact of three different frass doses (0, 2.5, and 5 tons/ha) on the growth of the Tsuruoka soybean variety (Glycine max L.), dadachamame. Results showed no significant differences in plant height (p =0.07), but higher doses increased leaf count (p<0.01) and SPAD values significantly (p<0.001), with 2.5 tons/ha improving leaf count by 26% and SPAD values by 16%. Yield analysis revealed that 2.5 tons/ha increased the number of filled pods by 29% (p<0.05) and reduced empty pods by 52% (p<0.001), thereby enhancing pod quality. Arthropod analysis indicated that 5 tons/ha significantly increased overall arthropod abundance (p<0.001), particularly predators (p<0.001) and herbivores (p<0.001), while 2.5 tons/ha balanced predator abundance, thereby controlling herbivores and supporting biodiversity. These findings suggest that an application dose of 2.5 tons/ha is optimal for improving edamame yield and quality while maintaining a balanced arthropod ecosystem, demonstrating black soldier fly frass as a nutrient-rich, eco-friendly input that supports sustainable agriculture.